2020
DOI: 10.3390/su12072654
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility to Food Retailers: The Case of Belo Horizonte, Brazil

Abstract: Access to food products is essential to sustain life. In this paper, we discuss the differences concerning accessibility levels to food retailers among potential consumers in Belo Horizonte, Brazil. The goal was to characterize spatial mismatches regarding opportunities to access food and identify suitable areas for sustainable last food mile solutions, such as non-motorized home delivery and purchase trips. For this, we have spatially related: (i) the population concentration; (ii) the income of households an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Despite the decline in on-site consumption, we observed that lunch and dinner consumption occurred more frequently among participants living in large cities and not practicing total social distancing. This trend may be attributed to the concentration of food services in large urban centers (Oliveira et al , 2020). Consequently, many individuals worked on-site and ate away from home, possibly in institutional food services, because governments worldwide mandated the closure of food business establishments.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the decline in on-site consumption, we observed that lunch and dinner consumption occurred more frequently among participants living in large cities and not practicing total social distancing. This trend may be attributed to the concentration of food services in large urban centers (Oliveira et al , 2020). Consequently, many individuals worked on-site and ate away from home, possibly in institutional food services, because governments worldwide mandated the closure of food business establishments.…”
Section: Discussionmentioning
confidence: 99%
“…A notable diversification emerged when analyzing the authorship of the 98 included studies. Six researchers- [48][49][50][51][52][53]-stood out, each contributing two articles on the covered topic, demonstrating a range of perspectives and expertise in the field. Among the selected articles, eight journals were particularly prominent, each publishing at least two.…”
Section: Convergence Codingmentioning
confidence: 99%
“…Based on the analysis of relevant literature, it can be stated that a complete achievement of sustainable LM freight delivery is hindered by a scarce consideration of the operational, environmental, societal, and economic requirements of the main stakeholders in the distribution chain [73]. Thus, the introduction of viable LM delivery solutions asks for more thorough analyses of the preferences, the VP that could satisfy the needs of the key process actors, and, above all, retailers, who constitute the vital final link with endconsumers [9]. In fact, to our best knowledge, the literature has so far paid poor attention to the quantification of the local retailers' needs, failing to provide guidelines about the levers for making LM delivery services sustainable and attractive for them.…”
Section: The Value Proposition Of Last-mile Delivery Innovationsmentioning
confidence: 99%
“…Thus, last-mile is not merely a logistics problem, but it has become a crucial urban planning challenge [7], with the ultimate goal of making the associated services sustainable from an operational, economic, and environmental point of view. As a matter of fact, the continuously increasing number of freight vehicles in urban areas undermines sustainability in the economic, societal, and metropolitan landscape [8,9]. Logistics activities are often outsourced to professional LSPs, and this decision has been the subject of a vast literature.…”
Section: Introductionmentioning
confidence: 99%